Rhabdomyosarcoma of the mandible in a 6-year-old boy - L. E. DAVIDSON, F. A. SOLDANI & S. NORTH (Paediatric Dentistry, 2006)
Rhabdomyosarcoma is an aggressive malignant tumour composed of neoplastic mesenchymal cells that infiltrate surrounding tissue structures, making their precise site of origin unclear.